2002
DOI: 10.1034/j.1600-0765.2002.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the chemokine interleukin‐8 and interleukin‐8 receptors in human gingiva and cultured gingival keratinocytes

Abstract: Interleukin-8 (IL-8) has been implicated in a wide variety of diseases. Previous studies have demonstrated the expression of IL-8 in periodontal tissues, yet little is known about the exact source(s), mechanisms and factors involved in gingival expression of IL-8. Additionally, nothing is known about the presence and distribution of IL-8 receptors (IL-8R) in gingival cells. Therefore it was hypothesized that, in vivo, periodontal pathogens induce IL-8 expression from gingival keratinocytes (GK) which enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…However, the results of the immunohistochemistry studies were inconsistent. Two of these studies [24,28] reported higher levels of IL-8 in individuals with periodontal disease and only 1 [27] study found higher levels of IL-8 in healthy tissues. The remaining 2 studies only evaluated the IL-8 presence in healthy or diseased gingival tissue, without comparing the IL-8 levels between individuals with and without CP.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of the immunohistochemistry studies were inconsistent. Two of these studies [24,28] reported higher levels of IL-8 in individuals with periodontal disease and only 1 [27] study found higher levels of IL-8 in healthy tissues. The remaining 2 studies only evaluated the IL-8 presence in healthy or diseased gingival tissue, without comparing the IL-8 levels between individuals with and without CP.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showing that IL-8 exerts mitogenic actions directly or by binding to its receptors on epithelial cells (31,32) lend support to our results. It is possible that IL-8, together with other cytokines and growth factors (25,33), could contribute to epithelial cell proliferation even in the early stage of endoscopy-negative GERD, and could be eventually linked to carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…IL-8 also exerted mitogenic actions directly or by binding to its receptors on epithelial cells [20,21] . Taken together, it is possible that IL-8, together with other cytokines as well as growth factors [14,22] , could contribute to epithelial cell proliferation even in NERD, and could be eventually linked to carcinogenesis. Again, unlike CXCR-1, CXCR-2 is not specific for IL-8 and can bind to other chemokines such as growth related oncogene α, but it has 2-to 5-fold higher affinity for IL-8 than CXCR-1 [19] .…”
Section: Discussionmentioning
confidence: 99%